2020
DOI: 10.1038/s41598-020-71742-z
|View full text |Cite
|
Sign up to set email alerts
|

Rapid, precise quantification of large DNA excisions and inversions by ddPCR

Abstract: The excision of genomic sequences using paired CRISPR-Cas nucleases is a powerful tool to study gene function, create disease models and holds promise for therapeutic gene editing. However, our understanding of the factors that favor efficient excision is limited by the lack of a rapid, accurate measurement of DNA excision outcomes that is free of amplification bias. Here, we introduce ddXR (droplet digital PCR eXcision Reporter), a method that enables the accurate and sensitive detection of excisions and inve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 39 publications
(47 reference statements)
2
12
0
Order By: Relevance
“…Canver et al (2014) estimated an overall deletion rate, across 17 targets of varying size, to occur at approximately one-third the rate of deletions (5.8% vs. 14.2%, respectively). A more recent study found this ratio to be approximately one-half (Watry et al 2020). We evaluated how this might affect our results.…”
Section: Inhibition Of Dna-pkcs During Dsb Formation Increases Crisprmentioning
confidence: 88%
See 2 more Smart Citations
“…Canver et al (2014) estimated an overall deletion rate, across 17 targets of varying size, to occur at approximately one-third the rate of deletions (5.8% vs. 14.2%, respectively). A more recent study found this ratio to be approximately one-half (Watry et al 2020). We evaluated how this might affect our results.…”
Section: Inhibition Of Dna-pkcs During Dsb Formation Increases Crisprmentioning
confidence: 88%
“…However, it is incapable of distinguishing deletion from inversion, the latter being a nonnegligible editing outcome. In the future, it will be important to use methods capable of distinguishing deletion and inversion events, such as digital droplet PCR (ddPCR) (Antoniani et al 2018;Watry et al 2020), although it might not be practical for testing large numbers of samples and conditions. Although the CiDER and qPCR assays used here could not explicitly distinguish the ratios of deletion and insertion arising from pgRNA targeting, we found that most of the measured iDNA-PKcs-dependent changes arise from increases in deletion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, inducing frameshifts at the site of mutations in distal coding exons may not be therapeutic, as nonsense codons in that context can lead to expression of a pathologic truncated protein rather than nonsense-mediated decay (Lindeboom et al, 2016; Stone et al, 2019). Alternate editing strategies for these mutations include excision of mutant alleles using pairs of guide RNAs, or precise correction using non-nuclease editing technologies such as base editors or PRIME editing (Watry et al, 2020; Komor et al, 2016; Anzalone et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…To overcome this challenge, we engineered patient-derived iPSCs with integrated, inducible, and isogenic (i 3 ) transcription factors in order to rapidly and efficiently differentiate them into lower motor neurons (i 3 LMNs) (Fernandopulle et al, 2018). We inserted a doxycycline-inducible cassette containing NGN2, ISL1, and LHX3 into the AAVS1 safe-harbor locus (Supplementary Figure 1) of a previously characterized CMT2E iPSC line with the NEFL N98S mutation, referred to here as N98S (Saporta et al, 2015;Maciel et al, 2020;Watry et al, 2020). For comparison, we used healthy control (WT) iPSC lines containing the same doxycycline-inducible cassette integrated into AAVS1 or CLYBL, as previously described (Fernandopulle et al, 2018;Shi et al, 2018).…”
Section: Rapid Development Of Cmt2e Phenotypes In Ipsc-derived Motor Neuronsmentioning
confidence: 99%